Pengaruh Pemberian EM4 Dengan Konsentrasi Berbeda Terhadap Lama Pelapukan Dan Kualitas Kompos Dari Limbah Dapur Organik Dalam Komposter Tertutup Skala Rumah Tangga - Putra Zai; Putra Zato Mendrofa (Jurnal Ilmu Pertanian dan Perikanan, 2025)
This study aims to determine the effect of Effective Microorganisms 4 (EM4) on the decomposition time and quality of compost made from household kitchen waste using a closed composting system. The research was conducted over 28 days at the researcher's home in Ahedano Village, Idanogawo Subdistrict, Nias Regency, using simple tools and materials. Three treatments were applied: no EM4 (control), 1% EM4, and 3% EM4 based on the weight of the organic waste. The kitchen waste consisted of vegetable scraps, fruit peels, and leftover food, which were chopped and composted in closed plastic buckets. Observed parameters included color changes, temperature, pH, texture, and compost odor. The results showed that EM4, especially at the 3% dosage, significantly accelerated decomposition and improved compost quality. The 3% EM4 treatment produced dark brown compost more quickly, reached a higher peak temperature (±44°C), stabilized pH near neutral (±7.5), and resulted in a finer texture with an earthy smell. In contrast, the control treatment decomposed more slowly and produced compost with a coarser texture and a stronger fermentation odor. In conclusion, the use of EM4 in simple home composting effectively accelerates the decomposition process and enhances compost quality. This method is suitable for household-scale organic waste management and supports the production of natural fertilizer in a practical, low-cost way.